2022
DOI: 10.1007/s12209-022-00320-3
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Spin Polarization of Defected Co3O4 for Highly Efficient Electrocatalysis

Abstract: Electrocatalytic water splitting is limited by kinetics-sluggish oxygen evolution, in which the activity of catalysts depends on their electronic structure. However, the influence of electron spin polarization on catalytic activity is ambiguous. Herein, we successfully regulate the spin polarization of Co3O4 catalysts by tuning the concentration of cobalt defects from 0.8 to 14.5%. X-ray absorption spectroscopy spectra and density functional theory calculations confirm that the spin polarization of Co3O4 is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The sample displayed small-sized Co nanoparticles regularly embedded in the silica matrix. The lattice spacing along a specific direction was 0.21 nm, which agrees with the (111) crystal plane of the cubic-phase Co [33,34]. The elemental mapping results confirmed the coating of silica and demonstrated the existence of a core-satellite structure (Fig.…”
Section: Resultssupporting
confidence: 74%
“…The sample displayed small-sized Co nanoparticles regularly embedded in the silica matrix. The lattice spacing along a specific direction was 0.21 nm, which agrees with the (111) crystal plane of the cubic-phase Co [33,34]. The elemental mapping results confirmed the coating of silica and demonstrated the existence of a core-satellite structure (Fig.…”
Section: Resultssupporting
confidence: 74%
“…However, further observation revealed that the oscillation amplitude of ZnFeO-CP-15 was slightly smaller than that of ZnFeO-C, suggesting that the former had a higher degree of disorder in the local coordination environment than the latter. 13 Both samples presented three dominant Fourier-transformed intensities (Fe–O, Fe–M 1 , and Fe–M 2 ) in the R -space, which correspond to the coordination of the Co–O, Fe ( O h )–M ( O h ), and Fe ( O h )–M ( T d ) or Fe ( T d )–M ( T d ) shells, respectively. 48,49 Compared with ZnFeO-C, the amplitudes of ZnFeO-CP-15 showed a decreasing trend at 2.60 and 3.16 Å.…”
Section: Resultsmentioning
confidence: 94%
“…5,6 However, due to their high cost, scarcity, and poor stability of noble metal catalysts, 3D transition metals and their derivatives have been extensively studied, with spinel and perovskite metal oxides being the most widely investigated. [7][8][9][10][11] Conventional OER mechanisms of spinel or perovskite catalysts follow the adsorbate evolution mechanism (AEM), 12,13 but most of the active sites in these catalysts are wasted. For example, in Co 3 O 4 , 14 1/3 of the cobalt occupies tetrahedral sites, and only this fraction can be used as active OER sites.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous reports, electron spin polarization could enhance the catalytic activity of OER, because the unique OER steps from singlet reactant to the triplet product (↑OO↑) call for a spin-selective electron transfer. 43–46 Furthermore, the Fe and Ni catalysts have excellent OER catalytic activity. It is worth noting here that Ni and Fe occupy different d-orbitals that determine the electron transfer rate and reaction thermodynamics, which are intrinsically dependent on the cation's spin state.…”
Section: Potential Factormentioning
confidence: 99%